Greenville : the history of the city and county in the South Carolina Piedmont - Huff, Archie Vernon, 1937- (University of South Carolina Press, 1995)
Since the Cherokee Nation hunted the verdant hills in what is now known as Greenville County, South Carolina, the search for economic prosperity and diversity has defined the history of this thriving Upstate region and its expanding urban center. In a sweeping chronicle of the city and county, historian Archie Vernon Huff traces Greenville's business tradition and details its political, religious, and cultural evolution. The region portrayed by Huff has historically defied many Southern norms to distinguish itself economically and ideologically from its neighbors. In addition to tracing Greenville's economic growth, Huff identifies other hallmarks of the region, including the fierce independence of its various populations. He discusses the often conflicting interests and the individual contributions of the area's African Americans, mill workers, business elite, and urban dwellers. Looking beyond but never straying far from the economics of the region, Huff also assesses the impact of Greenville's peaceful but grudging end to segregation, strong evangelical Protestant tradition, conservative arts programs, and influential role in South Carolina's emerging two-party political system.